Hearing Loss and Hearing Handicap in Users of Recreational Firearms - Stewart, Michael; Pankiw, Rebecca; Lehman, Mark E.; Simpson, Thomas H. (Journal of the American Academy of Audiology, 2002)
This investigation sought to establish the prevalence of hearing loss and hearing handicap in a population of 232 recreational firearm users. Hearing handicap was calculated based on four methods using pure-tone threshold data from the American Academy of Ophthalmology and Otolaryngology, American Academy of Otolaryngology-Head and Neck Surgery, National Institute of Occupational Safety and Health, and American Speech-Language and Hearing Association in addition to the self-report Hearing Handicap Inventory for Adults-Screener (HHIA-S). Subjects (45 female and 187 male) ranging in age from 13 to 77 years (mean = 40 years, SD = 15.1) completed a short questionnaire regarding demographics and shooting practices followed by pure-tone air audiometry at Occupational Safety and Health Administration test frequencies of 500 to 6000 Hz. A total of 177 who exhibited varying degrees of hearing loss also received a face-to-face administration of the HHIA-S. Audiometric and HHIA-S results revealed that both high-frequency hearing loss and hearing handicap varied significantly as functions of age and occupation. Significant gender effects were observed audiometrically but not as a function of hearing handicap. HHIA-S scores varied significantly as a function of high-frequency (1000–4000 Hz) hearing loss. Correlation coefficients between the four different pure-tone methods of calculating hearing handicap and the self-reported HHIA-S were highest for pure-tone methods that do not employ 500 Hz in the calculation.
Keywords: Firearm users; gender; hearing handicap; high-frequency hearing loss; noise-induced hearing loss; pure-tone average